2006
DOI: 10.1080/13693780500160793
|View full text |Cite
|
Sign up to set email alerts
|

Infection in a neonate caused byPichia fabianii: Importance of molecular identification

Abstract: Pichiafabianii, an uncommon yeast species recovered from clinical specimens, was documented as the cause of an infection in a 5-week-old female twin delivered at 25 and 3/7 weeks. She developed respiratory distress syndrome and necrotizing enterocolitis. At the time of the infection, she was febrile, thrombocytopenic, and still was requiring minimal ventilatory support. Blood cultures drawn on two consecutive days were positive for a germ tube negative yeast. Phenotypic methods including carbohydrate fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 8 publications
1
35
1
Order By: Relevance
“…Interestingly, and in agreement with our observation (Table 3), in the endocarditis case reported by Hamal et al (16), the isolates were initially identified biochemically as Candida pelliculosa; however, on the basis of direct sequencing of the internal transcribed spacer region of rRNA, they were subsequently reidentified as Pichia fabianii with strong biofilm formation and voriconazole resistance. Pichia fabianii is an example of a yeast species which requires molecular techniques for correct identification (5).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, and in agreement with our observation (Table 3), in the endocarditis case reported by Hamal et al (16), the isolates were initially identified biochemically as Candida pelliculosa; however, on the basis of direct sequencing of the internal transcribed spacer region of rRNA, they were subsequently reidentified as Pichia fabianii with strong biofilm formation and voriconazole resistance. Pichia fabianii is an example of a yeast species which requires molecular techniques for correct identification (5).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional identification of yeasts relies upon a combination of morphological and biochemical features using tests that may require relatively long periods of incubation, are labor intensive and/or require subjective interpretation. Popular biochemical identification panels such as API 20C AUX or VITEK ID-YST (BioMerieux, Durham N.C) may have limited databases resulting in misidentification of some isolates [6][7][8][9]. Therefore, molecular methods offer an attractive, accurate and rapid alternative for the identification of pathogenic yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that such methods frequently fail to identify the less common pathogens and those common organisms that are misbehaving (1,15) or to discriminate between closely related species (15,27). Molecular identification, employing PCR amplification and sequencing of genomic regions that evolve slowly and that show high degrees of conservation, represents a rapid and sensitive alternative to conventional identification for yeasts and is also useful for the establishment of phylogenetic relationships.…”
mentioning
confidence: 99%